2023
DOI: 10.3389/fneur.2023.1118563
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of dynamic neutrophil-to-lymphocyte ratio in acute ischemic stroke after reperfusion therapy: A meta-analysis

et al.

Abstract: BackgroundThe prognostic role of the neutrophil-to-lymphocyte ratio (NLR), an inflammatory marker, in acute ischemic stroke (AIS) after reperfusion therapy remains controversial. Therefore, this meta-analysis sought to assess the correlation between the dynamic NLR and the clinical outcomes of patients with AIS after reperfusion therapy.MethodsPubMed, Web of Science, and Embase databases were searched to identify relevant literature from their inception to 27 October 2022. The clinical outcomes of interest inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…This cut-off was supported by recent studies demonstrating higher mortality and infectious complications in stroke patients with a ≥ 5 NLR 9 , 15 17 . Altogether, this data consistently suggests that NLR ≥ 5 may be considered a proper marker of SII, associated with post-stroke mortality, short-term global outcome (modified Rankin Scale), intracerebral haemorrhage (ICH), rate of infectious complications, and post-stroke depression 10 14 . The majority of available evidence on SII is derived from acute phase studies.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…This cut-off was supported by recent studies demonstrating higher mortality and infectious complications in stroke patients with a ≥ 5 NLR 9 , 15 17 . Altogether, this data consistently suggests that NLR ≥ 5 may be considered a proper marker of SII, associated with post-stroke mortality, short-term global outcome (modified Rankin Scale), intracerebral haemorrhage (ICH), rate of infectious complications, and post-stroke depression 10 14 . The majority of available evidence on SII is derived from acute phase studies.…”
Section: Introductionmentioning
confidence: 70%
“…Previous studies found higher NLR values in the acute phase of ischemic or haemorrhagic stroke 6 9 . The clinical role of NLR in patients with acute stroke admitted to the intensive care setting has been detailed in several recent systematic reviews and meta-analyses 10 14 . Although a definite consensus is lacking, the presence of SII seems consistent in patients with a NLR ≥ 5 9 , 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The thromboinflammatory response has been observed in all phases of AIS [ [13] , [14] , [15] ]. Importantly, this process can also occur in patients who initially achieve successful mechanical recanalization, potentially leading to secondary tissue damage and exacerbating stroke outcomes [ 14 , 36 , 37 ]. Previous study has also demonstrated that patients undergoing EVT are more likely to experience significant dynamic changes in a variety of immune indices compared to those receiving IVT alone [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that day 1 SII and AISI were independent predictors of 90-day functional outcome, while day 1 SII and SIRI served as independent predictors of sICH occurrence. These markers are derived from the well-established NLR, may partially explain their predictive capacities [ 37 ]. Given that these markers offer a comprehensive reflection of the host's inflammatory, immune, and thrombotic status, and have shown superior predictive ability compared to single-cell counts and variables based on two cell subtypes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation